Mapping sweet potato in Eastern Africa - Gichuki, Simon T.; Hijmans, Robert J. (Technical Centre for Agricultural and Rural Cooperation, 2005)
Simon T. Gichuki and Robert J. Hijmans report on a project that is collecting germplasm samples and local knowledge of sweet potato varieties in Eastern Africa with the help of DIVA-GIS, a free geographic information system (GIS).